Incidence of Postoperative Complications among Patients with Active or Resolved COVID-19 Undergoing Elective Abdominal Wall Reconstruction - Fabiola Aguilera, MD; Grant Wagner, BS; Madeline Bald, BS; Joshua Richman, MD, PhD; Jorge I. de la Torre, MD, FACS, MSHA (Plastic and Reconstructive Surgery, Global Open)
Background:. The incidence of postoperative complications among patients with coronavirus disease 2019 (COVID-19) positivity undergoing elective surgical operations is poorly understood. This study aimed to identify differences in postoperative complications after elective abdominal wall reconstruction (AWR) in patients diagnosed with COVID-19 compared with patients presenting prepandemic. Methods:. A single-institution, retrospective chart review was performed of patients undergoing AWR between January 2017 and September 2022. Patients were stratified by date: pre-COVID-19 (January 2017 to December 2019) and post-COVID-19 (January 2020 to September 2022). Patients confirmed as COVID-19-positive were also identified. Data collected included demographics, clinical characteristics, and complications. Univariate and multivariate analyses were performed. Results:. We included 168 patients. The mean age was 54 years, and the mean body mass index was 33 kg/m2. Seventy-five patients underwent surgery pre-COVID-19 and 93 patients after. Of 93 patients, 16 (17%) had a positive COVID-19 test before surgery or during the perioperative period. These 2 groups were risk-matched. Patients with COVID-19 had no significant increase in postoperative complications. Major complications occurred at 13.3% in the pre-COVID-19 group and 7.5% in the post-COVID-19 group. Patients with COVID-19 were more likely to be younger (48 versus 57; P = 0.049) and more likely to have a shorter length of stay in the hospital (3 versus 5.8; P = 0.038). Conclusions:. In our case series, there was an associated increase in the incidence of overall pulmonary-related complications in the postpandemic group. This study is limited by its small sample size. Further investigation should be carried out on this topic.